(w-8)(3w+7)=0

Simple and best practice solution for (w-8)(3w+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w-8)(3w+7)=0 equation:


Simplifying
(w + -8)(3w + 7) = 0

Reorder the terms:
(-8 + w)(3w + 7) = 0

Reorder the terms:
(-8 + w)(7 + 3w) = 0

Multiply (-8 + w) * (7 + 3w)
(-8(7 + 3w) + w(7 + 3w)) = 0
((7 * -8 + 3w * -8) + w(7 + 3w)) = 0
((-56 + -24w) + w(7 + 3w)) = 0
(-56 + -24w + (7 * w + 3w * w)) = 0
(-56 + -24w + (7w + 3w2)) = 0

Combine like terms: -24w + 7w = -17w
(-56 + -17w + 3w2) = 0

Solving
-56 + -17w + 3w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(-7 + -3w)(8 + -1w) = 0

Subproblem 1

Set the factor '(-7 + -3w)' equal to zero and attempt to solve: Simplifying -7 + -3w = 0 Solving -7 + -3w = 0 Move all terms containing w to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3w = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3w = 0 + 7 -3w = 0 + 7 Combine like terms: 0 + 7 = 7 -3w = 7 Divide each side by '-3'. w = -2.333333333 Simplifying w = -2.333333333

Subproblem 2

Set the factor '(8 + -1w)' equal to zero and attempt to solve: Simplifying 8 + -1w = 0 Solving 8 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1w = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1w = 0 + -8 -1w = 0 + -8 Combine like terms: 0 + -8 = -8 -1w = -8 Divide each side by '-1'. w = 8 Simplifying w = 8

Solution

w = {-2.333333333, 8}

See similar equations:

| 4-(2x+3)=5x-8 | | 1=v-8 | | -5-4r=-(1-2r) | | -9=2+p | | 8x-(5-x)+2(3x-4)=2 | | 3x^2=-18 | | 3r-4=5(r-1) | | 3k=45 | | 2(7/2)+y=11 | | 3(x-2)=-31+4x | | 8m+m-m-3m+2m=14 | | 3(2x+5)-5= | | 19s-13s-6s+s=19 | | 8.8=m-14.4 | | 7x+2y=94 | | 152+8x=-82-10x | | v^2-5vy-14y^2=0 | | 5r-1=-3(-4+3r)+r | | 2y=7x-94 | | (2s-9)(8s+1)=0 | | 19s-13s-6s=19 | | 3c+2=6c | | 5(m+9)=40+2m+5+3m | | 10x^2=60x+2 | | 4+2(x-8)=8-4x+2 | | -(6x-2y-2)= | | 42s+s^2-s^3=0 | | 6x+9=9x-6 | | 84=12n | | (6t-7)(t+6)=0 | | log(2t+4)=log(13-3t) | | 20+b-b^2=0 |

Equations solver categories